Optimalisasi Kualitas Pelayanan Front Office Department Di Masa New Normal Terhadap Kepuasan Tamu: Studi Kasus : The Royal Surakarta Heritage MGallery by Sofitel - Elizabet Sagala, Afrilia (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
Optimizing the quality of service during the new normal for guest satisfaction at The Royal Surakarta Heritage MGallery by Sofitel ". The object of this research is the front office department, and the type of method used is the descriptive qualitative method. The data in this study were collected by data collection techniques such as observation, interviews, and documentation. The resource persons taken were front office officers, operational managers, and hotel guests. The technique of data validity uses triangulation technique, source, and time. There is a difference between before and after a pandemic. The service quality contains 5 dimensions including Tangibles (physical evidence), Reliability (reliability), Responsiveness (responsiveness), assurance (Assurance), and Empathy (empathy). The conclusion from this research is that the dimensions of tangibles, responsiveness, assurance, and empathy have met the expectations of guests so that guests can be said to be satisfied. However, the reliability of the front office cannot be said to be satisfactory because the accuracy in housekeeping provides rooms so that it occurs in the lobby which causes not keeping a distance.